Frequency of Gall Bladder Carcinoma Among Patients Presenting with Cholelithiasis - Hayat, Faisal; Haque, Anwar Ul (Biological and Clinical Sciences Research Journal, 2025)
Gallbladder carcinoma is an uncommon but aggressive malignancy that is frequently associated with long-standing cholelithiasis and is often diagnosed incidentally on histopathology after cholecystectomy. Objective: To determine the frequency of gall bladder carcinoma among patients with cholelithiasis presenting at Saidu Group of Teaching Hospital, Swat. Methodology: One hundred seventy-five patients aged 25 to 70 years presenting with cholelithiasis were enrolled in this study. All the patients underwent laparoscopic cholecystectomy. Every gallbladder was assessed for histopathological examination, and patients were evaluated clinically for jaundice, abdominal pain, and unexplained weight loss. Data analysis was performed using SPSS 23. Results: The mean age of the cohort in the present study was 46.06 ± 13.66 years, while the mean BMI was 25.65 ± 1.77 kg/m2. The study cohort had 133 females (76.0%) and 42 males (24.0%). Most of the patients resided in urban areas (63.4%) and belonged to the middle socioeconomic class (43.4%). Histopathological examination showed that gallbladder carcinoma was present in 6 patients (3.4%). Gallbladder carcinoma did not show an association with demographics. Conclusion: The frequency of gallbladder carcinoma in patients with cholelithiasis in the present study was 3.4%.